É conhecendo que se entende: desmistificando as produções científicas sobre autismo - SILVA, Gabriel Martins (2024)
This work is the result of the experiences of the present authors throughout their journeys in the Full Degree in Mathematics. The choice of the theme regarding the teaching of mathematics to autistic students was not a random choice, but rather, built and inspired in the midst of the events that occurred during this incredible event. However, this work is composed by the junction of two Book Chapters published in E-books. Chapter I sought to indicate possible solutions for autistic students to learn mathematics. To achieve this research, the technique of bibliographic analysis was used, this technique, according to Gil (2002, p. 44), is developed based on materials already available, consisting mainly of books and scientific articles. The locus of this research was the annals of the 2019 and 2020 editions of the National Meeting of Inclusive Mathematics Education (ENEMI). After the search, a corpus was formed, with a total of 18 articles. And with the reading of the articles, tables were created grouping the works among them by similarity based on selected thematic axes. However, after the analysis of the articles, it was understood that for the inclusion of autistic students to be adequate, three basic conditions are necessary, namely: 1) Know and study the characteristics common to people with autism; 2) Define the form of educational assistance to be offered, concomitantly with the common class; and 3) Develop appropriate pedagogical strategies in the classroom, responding to the special educational needs of students with autism, which should be systematically evaluated (MENEZES, 2012; PLETSCH, 2014). Chapter II investigated the scientific productions, with emphasis on Elementary School 1 and 2, on the teaching of Mathematics directed to autistic individuals. This objective was achieved through a bibliographic research that, according to Sampieri, Collado and Lucio (2013), is mainly based on secondary sources, which are works that synthesize and interpret information from primary sources as original research studies. For the data collection of this study, the renowned digital platforms were used: Coordination for the Improvement of Higher Education Personnel (CAPES) and the Brazilian Digital Library of Theses and Dissertations (BDTD), and there was a selection of 24 works, 20 dissertations and 2 theses. Data were analyzed using the techniques of Booth, Sutton, and Papaioannou (2016), which involve the identification of relevant studies, systematization of information, grouping and categorization, synthesis, and critical analysis. In short, some of the results highlighted with Figure 1 that studies aimed at teaching mathematics to autistic students are recent, with a higher rate in 2020. It is worth noting that the Southeast is the region that predominated in relation to the number of publications found in Chapters I and II. Therefore, writing this work as a whole has unleashed valuable knowledge for the training of the present authors as future professionals qualified to exercise the profession with excellence, and that they are grateful for contributing to the scientific community.